Variation in freshwater fish assemblages along a regional elevation gradient in the northern Andes, Colombia. Issue 13 (4th June 2015) - Carvajal‐Quintero, Juan D.; Escobar, Federico; Alvarado, Fredy; Villa‐Navarro, Francisco A.; Jaramillo‐Villa, Úrsula; Maldonado‐Ocampo, Javier A.
Abstract Studies on elevation diversity gradients have covered a large number of taxa and regions throughout the world; however, studies of freshwater fish are scarce and restricted to examining their changes along a specific gradient. These studies have reported a monotonic decrease in species richness with increasing elevation, but ignore the high taxonomic differentiation of each headwater assemblage that may generate high β‐diversity among them. Here, we analyzed how fish assemblages vary with elevation among regional elevation bands, and how these changes are related to four environmental clines and to changes in the distribution, habitat use, and the morphology of fish species. Using a standardized field sampling technique, we assessed three different diversity and two structural assemblage measures across six regional elevation bands located in the northern Andes (Colombia). Each species was assigned to a functional group based on its body shape, habitat use, morphological, and/or behavioral adaptations. Additionally, at each sampling site, we measured four environmental variables. Our analyses showed: (1) After a monotonic decrease in species richness, we detected an increase in richness in the upper part of the gradient; (2) diversity patterns vary depending on the diversity measure used; (3) diversity patterns can be attributed to changes in species distribution and in the richness and proportions of functional groups along the regional elevation gradient; and (4) diversity patterns and changes in functional groups are highly correlated with variations in environmental variables, which also vary with elevation. These results suggest a novel pattern of variation in species richness with elevation: Species richness increases at the headwaters of the northern Andes owing to the cumulative number of endemic species there. This highlights the need for large‐scale studies and has important implications for the aquatic conservation of the region.